Crimes of the senses: yarn bombing and aesthetic criminology - Millie, Andrew (The British journal of criminology, 2019)
Yarn bombing involves the display of knitted or crocheted items in public space, often without permission. This article draws on interviews with yarn bombers in the North West of England and considers who the yarn bombers are, their motivations and experiences and their views on the legal status of yarn bombing. Although the visual is important for yarn bombing—and it is therefore of interest to visual criminology—this article also looks further to consider other sensory experience. In this way, it contributes to an emerging aesthetic criminology concerned with broader sensory, affective and emotive experience. Drawing on Thrift’s work on urban affect or mood, as well as Anderson and Young on affective atmospheres, yarn bombing is regarded as a crime of the senses affecting both the look and the feel of the city. The scope for further development of an aesthetic criminology is suggested, including specific methodologies that embrace the full range of sensory experiences associated with crime, disorder or social harm.